The Development of Teaching Materials of Learning Evaluation Based on Whole Language Learning for Students at the Indonesian Language and Literature Education Study Program - Andiopenta Andiopenta (STAI Hubbulwathan Duri, 2023)
This study aims to foster teaching materials for the evaluation of Indonesian language learning based on the Whole Language. The research applied the research and development (RD) method from Borg Gall. The test subjects were 2021/2022 semester students, as many as 25 people for the experimental and 25 for control classes. Data analysis techniques in this study included analysis of data validity by experts, including material content experts, graphic design experts, and linguists, who were analyzed using descriptive statistics to obtain percentages and average figures. As for the difference test between before and after using teaching materials through the t-test. The triangulation technique used is technique, source, and theory triangulation. The research results on syllabus alignment with student needs show an average of 94% to 100% appropriate. The results of the validation of the content of the material averaged 4.33 in the good category, the average graphic design was 4.61 in the good category, and the elements of language were 4.31 in the good category. The results of product trials before use averaged 5.35. After use it became 6.01. The second stage of trials, before using teaching materials was 5.60, after using 6.01. The third stage trial was before using 5.85 and after 6.14. The difference test between before and after using teaching materials shows a significant difference between the t-test and t-table, through the t-test namely on learning motivation 6,717 1,686 learning creativity 6,886 1,686 and learning outcomes 6,747 1,686, indicating there is a significant difference. Thus, the hypothesis is accepted, this means that the use of study material books has a significant effect on students in learning Indonesian language learning evaluation courses.